2010
DOI: 10.1021/ic100944d
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Copper(I) Complexes Containing Cyclodiphosphazane Derivatives and Pyridyl Ligands: Synthesis, Structural Studies, and Antiproliferative Activity toward Human Cervical and Breast Cancer Cells

Abstract: Several mixed-ligand copper(I) complexes of cyclodiphosphazanes, [(t)BuNP(NC(4)H(8)X)](2) (1, X = O; 2, X = NMe), were synthesized by reacting the octanuclear copper(I) complexes [Cu(8)(μ(2)-I)(8){[(t)BuNP(NC(4)H(8)X)](2)}(4)] (3, X = O; 4, X = NMe) with various pyridyl ligands. Interaction of the metallomacrocyclic complex 3 or 4 with pyridine, 2,2'-bipyridine, and 1,10-phenanthroline afforded the neutral dinuclear complexes [(C(5)H(5)N)(4)Cu(2)I(2){[(t)BuNP(NC(4)H(8)X)](2)}] (5, X = O; 6, X = NMe), [(2,2'-bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…First, phosphanes derived from aminoacids [6][7][8][9] or prepared from the highly water-soluble aliphatic secondary amines [10] seem to be most interesting in terms of formation of potential conjugates with a wide range of biomolecules. Second, a number of copper(I) complexes with tertiary phosphanes and diphosphanes showed a promising biological activity [11][12][13][14][15][16][17][18][19][20]. Additionally, it has been proven, that the use of the water soluble phosphanes is reasonable because their hydrophilic and labile complexes with copper(I) are more active against a panel of human tumor cell lines than the complexes with chelating diphosphanes [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…First, phosphanes derived from aminoacids [6][7][8][9] or prepared from the highly water-soluble aliphatic secondary amines [10] seem to be most interesting in terms of formation of potential conjugates with a wide range of biomolecules. Second, a number of copper(I) complexes with tertiary phosphanes and diphosphanes showed a promising biological activity [11][12][13][14][15][16][17][18][19][20]. Additionally, it has been proven, that the use of the water soluble phosphanes is reasonable because their hydrophilic and labile complexes with copper(I) are more active against a panel of human tumor cell lines than the complexes with chelating diphosphanes [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is present in all living organisms and is essential for growth and development, oxidative phosphorylation and DNA synthesis [3,4]. Being a vital element, the use of copper as anticancer agent supposedly causes lower toxicity than non-essential metals, such as platinum [4,5]. The properties of copper complexes are determined by the nature of chelates, which could have antiproliferative activity themselves [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Copper complexes with pyridyl ligands, like 2,2′-bipyridine and 1,10-phenanthroline, form stable chelates with moderate antiproliferative activity [5]. Other ligands, such as terpyridine, are also able to improve the stability of copper complexes and promote insertion of either planar pyridyl or aromatic ring between base pairs of the DNA, where the copper acts both as an anchor and reactive agent [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentration of copper in cancerous tissues such as breast, prostate, lung, and brain, is higher than that of the normal tissues [32][33][34]. Recently it has been reported that pyridyl-type ligand [35] and copper(II) terpyridyl complexes show moderate anticancer activities [36,37]. Complexes of these ligands would be good candidates for examination of their effect on cell proliferation.…”
Section: Introductionmentioning
confidence: 99%